Calculation of optical gain in AlGaN quantum wells for ultraviolet emission - Witzigmann, Bernd; Roemer, Friedhard; Martens, Martin; Kuhn, Christian; Wernicke, Tim; Kneissl, Michael (AIP Advances, 2020)
Stimulated emission from AlGaN based quantum wells (QWs) emitting at ultraviolet wavelengths is investigated theoretically. Maxwell-Bloch equations in the second Born approximation are solved self-consistently with the Poisson equation. The valence band dispersion is obtained from a 6-band kp-model. For a QW emitting at around 270 nm with a thickness of 2.2 nm, an estimated FWHM of 10 meV for homogeneous broadening and an excitonic red shift of 100 meV are extracted under typical laser conditions. From a comparison to experimental data of stimulated emission, an inhomogeneous broadening energy of 39 meV FWHM is evaluated. Calculations show that high TE gain can be achieved for thin QWs around 2 nm thickness in a multiple QW arrangement or for single QWs thicker than 6 nm.
CRIS-Team Scopus Importer:2021-06-11